2005
DOI: 10.1007/s00383-005-1601-8
|View full text |Cite
|
Sign up to set email alerts
|

Amyand’s hernia presenting as neonatal testicular ischaemia

Abstract: Testicular ischaemia presenting in the neonatal period is most often attributable to neonatal torsion. We present an unusual case of a male neonate who presented with acute appendicitis within a patent processus vaginalis, causing cord compression and consequent testicular ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
(9 reference statements)
0
15
0
1
Order By: Relevance
“…History and physical examination are suggestive of an incarcerated or strangulated right inguinal hernia. However, the signs and symptoms may mimic inguinal lymphadenitis, epididymo-orchitis, hydrocele of the spermatic cord, and testicular torsion [2,6,[13][14][15]. Patients often complain of crampy, dull, lower abdominal pain combined with an irreducible, tender mass in or near the inguinal canal.…”
Section: Discussionmentioning
confidence: 95%
“…History and physical examination are suggestive of an incarcerated or strangulated right inguinal hernia. However, the signs and symptoms may mimic inguinal lymphadenitis, epididymo-orchitis, hydrocele of the spermatic cord, and testicular torsion [2,6,[13][14][15]. Patients often complain of crampy, dull, lower abdominal pain combined with an irreducible, tender mass in or near the inguinal canal.…”
Section: Discussionmentioning
confidence: 95%
“…reported that perforation of an Amyand’s hernia can cause a peri-appendicular abscess [11]. This type of hernia can also present with testicular ischemia in newborn babies [12], hyperemia, and hemorrhagic infiltration into the hernia sac [13]. Francko et al .…”
Section: Discussionmentioning
confidence: 99%
“…Serrano and Ackerman reported an incarcerated right inguinal hernia that contained a perforated appendix along with an inflamed right testicle and spermatic cord; all of which had to be removed [20]. Amyand’s hernia with perforated appendix can present with testicular ischemia in neonates as well [21]. Strangulated Amyand’s hernia has been reported with hyperemia and hemorrhagic infiltration within the hernial sac [22].…”
Section: Clinical Presentationmentioning
confidence: 99%